2002
DOI: 10.1172/jci200214071
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel breast carcinoma–associated BA46-derived peptides in HLA-A2.1/Db-β2mtransgenic mice

Abstract: The human milk fat globule membrane protein BA46 (lactadherin) is highly overexpressed in human breast tumors, making it a potential target for tumor immunotherapy. We have identified BA46-derived peptides that contain the motif recognized by the MHC class I molecule HLA-A2.1 and that are processed and presented by human breast carcinoma cells. In mice lacking normal class I molecules but expressing an HLA-A2.1/D(b)-beta2 microglobulin single chain (HHD mice), three peptides elicited specific CTL activity. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The immunogenic potential of the MAGE-A8 peptides was examined in three vaccination modes; peptides delivered intranasally with CT as a mucosal adjuvant, peptides in complete Freund's adjuvant (CFA) injected to the tail base, and peptide loaded on RMA-S/HHD/B7 cells injected intraparitoneally ( Figure 3A -C, respectively). All these modes of vaccination were proven to give efficient immunisation in mice (Porgador et al, 1997;Carmon et al, 2002;Firat et al, 2002). Taking into account that peptides 8.1 and 8.3 were immunogenic in more than one mode of vaccination, we decided to further investigate the potential of peptides 8.1 and 8.3 to serve as TAA epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunogenic potential of the MAGE-A8 peptides was examined in three vaccination modes; peptides delivered intranasally with CT as a mucosal adjuvant, peptides in complete Freund's adjuvant (CFA) injected to the tail base, and peptide loaded on RMA-S/HHD/B7 cells injected intraparitoneally ( Figure 3A -C, respectively). All these modes of vaccination were proven to give efficient immunisation in mice (Porgador et al, 1997;Carmon et al, 2002;Firat et al, 2002). Taking into account that peptides 8.1 and 8.3 were immunogenic in more than one mode of vaccination, we decided to further investigate the potential of peptides 8.1 and 8.3 to serve as TAA epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-A2.1 is the most widespread allele of HLA in the human population, therefore our allele of choice for the search of tumour CTL epitopes. The HHD system enabled the identification of TAA of breast carcinoma (Carmon et al, 2000(Carmon et al, , 2002, and colon carcinoma (Tirosh et al, 2003). A MAGE-A1 epitope of HLA-A2.1 was recently identified (Pascolo et al, 2001), as well as shared epitopes of MAGE genes (Graff-Dubois et al, 2002).…”
mentioning
confidence: 99%
“…Because MFG-E8 is expressed at high levels in diverse tumor types (14,15), including melanoma, this soluble protein might serve as a general target for cancer therapy. In contrast to most oncologic treatments, which primarily address either the tumor or host separately, MFG-E8 antagonists might affect both compartments.…”
Section: Mfg-e8 Blockade Enhances Drug-induced Apoptosismentioning
confidence: 99%
“…9,10 The main amyloid fibril protein is medin (or AMed), which is a 50 amino-acid residue internal cleavage product of the precursor protein lactadherin. 11 Lactadherin is a 364 amino-acid residue protein found in many tissues [11][12][13][14] and has many proposed functions. 13,[15][16][17] To these functions we have added the ability of lactadherin to bind to elastin, and we have suggested that lactadherin acts as a linker between smooth muscle cells and elastin through its RGD-sequence at the N-terminal part and its medin part close to the C terminus.…”
mentioning
confidence: 99%